An Efficient Palladium N‐Heterocyclic Carbene Catalyst Allowing the Suzuki–Miyaura Cross‐Coupling of Aryl Chlorides and Arylboronic Acids at Room Temperature in Aqueous Solution. Issue 8 (15th April 2014) - Rajabi, Fatemeh; Thiel, Werner R.
Abstract The application of a highly active Pd‐NHC catalyst for the Suzuki–Miyaura cross‐coupling of a broad variety of electronically activated and deactivated aryl chlorides with different arylboronic acids in excellent yields is described. This catalyst can be handled under aerobic conditions, is active with low catalyst loadings at room temperature and in an aqueous reaction medium and allows the application of cheap potassium carbonate as the base. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>